Genre, féminismes et développement: une trilogie en construction - Levy, Charmain; Martinez, Andrea (Les Presses de l'Université d'Ottawa, 2019)
Cet ouvrage pédagogique multidisciplinaire conçu pour les cours de premier cycle présente les principaux enjeux théoriques et pratiques de l'heure en matière de genre, féminismes et développement. Misant sur la capacité d'agir et le pouvoir de transformation sociale des femmes des Suds, ce livre examine les enjeux du genre et du développement. Ce manuel féministe, clair et facile à consulter, est spécifiquement conçu pour les cours de premier cycle universitaire sur les femmes, le genre et le développement international. Organisé en sept sections, il offre un panorama aussi vaste que possible des préoccupations féministes reliées au genre et au développement, alimentant ainsi les réflexions et les études de cas dans le domaine. Issu du colloque « État des lieux sur les perspectives féministes en développement international » du Congrès international des recherches féministes dans la francophonie (CIRFF), l'ouvrage propose des contributions de professeures-chercheuses et de militantes européennes, canadiennes et des Suds dédiées à l'avancement des connaissances féministes, à leur diffusion plus large et à leur vulgarisation. Publié en français
Les chapitres Nagels, Nora. “Femmes, Travail Du Care et Néocolonialisme.”, Catarino, Christine, 2019. “Genre, Mondialisation et Migrations.” et Wills, Emily Regan, et al., 2019. “Conflits, Flux Migratoires et Exils Forcés.” ont été donnés en lecture au cours POL4022.
Keywords: afro-féminisme; approches et analyses; care; corps; cours; discipline; droits des femmes*; féminisme décolonial; féminisme postcolonial; histoire et politique; intersectionnalité; justice reproductive; outils; ouvrages de références; pol4022; premier cycle; ressource en ligne; santé; science politique; science politique et droit; thématiques; travail; violences; violences sexistes et sexuelles

Autoethnography as feminist method: Sensiting the feminist 'I' - Ettorre, Elizabeth (Routledge, 2018)
Autoethnography is an ideal method to study the ‘feminist I’. Through personal stories, the author reflects on how feminists negotiate agency and the effect this has on one's political sensibilities. Speaking about oneself transforms into stories of political responsibility - a key issue for feminists who function as cultural mediators.
Keywords: approches et analyses; corps; ethnographie; méthodologie; outils; ouvrages de références; point de vue situé; santé; thématiques

The Routledge handbook of gender and violence - Lombard, Nancy (Routledge, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice–one of the most important and ground-breaking subjects to have emerged in philosophy in recent years–refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Le chap 10 de Patricia Hill Collins, “Intersectionality and Epistemic Injustice” a été donné en lcture au cours FEM9000. Le chap 14 de Kim Hall, “Queer Epistemology and Epistemic Injustice” a été donné en lecture au cours FEM9000. Le chap 15 de Rachel McKinnon, “Allies behaving badly: Gaslighting as epistemic injustice” a été donné en lecture au cours FEM9000. Le chap 16 de Shelley Tremain, “Knowing Disability Differently” a été donné au cours FEM9000. Le chap 33 de Anastasia Scrutton, “Epistemic Injustice and Mental Illness” a été donné en lecture au cours FEM9000. Le chap 34 de Rebecca Tsosie, “Indigenous peoples, anthropology, and the legacy of epistemic injustice” a été donné au cours FEM9000.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap

Routledge handbook of sexuality, health and rights - Aggleton, Peter; Parker, Richard Guy (Routledge, 2010)
This handbook surveys the state of the discipline, including examination and discussion of emerging, controversial and cutting edge areas. It is an essential reference for all academics and researchers in the fields of sexuality studies, sexual health and human rights, as well as very useful reading for more advanced students.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; droits; outils; ouvrages de références; périodes historiques; santé; santé reproductive; sexualité; thématiques